The Monetary and Fiscal Policies on International Trade in Indonesia - Rangkuty, Dewi Mahrani; Nasution, Lia Nazliana; Hasyyati, Zata; Siregar, Sulisna Dewi; Firmansyah, Didi (The Es Economics and Entrepreneurship, 2024)
This study is to analyze how monetary and fiscal policies contribute to trade performance in Indonesia. The specific target of this study is to analyze the contribution and influence of variables such as exchange rate, inflation, trade balance, government expenditure, Tax, and investment in the short, medium and long term in Indonesia. So that it can show how much the contribution and influence of monetary and fiscal variables on trade performance in Indonesia. The results of this study explain that the largest contribution to the trade balance is the government expenditure and investment in the previous period, the largest contribution to inflation is the government expenditure and investment in the previous period, the largest contribution to government expenditure is the exchange rate and government expenditure itself in the previous period, the largest contribution to investment is government expenditure and investment itself in the previous period, the largest contribution to the exchange rate is the exchange rate itself and investment in the previous period, the largest contribution to Tax is government expenditure and exchange rate in the previous period.